KEBERADAAN YOUTH JAZZ COMMUNITY DI KOTA MEDAN - William B. Nababan (Grenek: Jurnal Seni Musik, 2013)
This research is intend to find out Youth Jazz Community existence in Medan, be in members, band and every activity that Youth Jazz Community do.Theory used includes the notion of the existence,development and community. The research method used is descriptive qualitative role in the study population is a resource that is a Youth Jazz Community. While the sample were 30 persons. To compliment the data’s in this study researchers conducted observation, interviews and documentation as well as the study of literatures. The research conducted in sei petani street 20th Medan. Youth Jazz Community is a community in wich there are a bunch of young people to jazz fan’s, they joined in a community that aims to popularize jazz music in Medan. The community began to take shape in 2010 and still active up to now. This community has a lot to hold and follow jazz event in Medan, they do this so that people in Medan can enjoy jazz music easily. This community event will be held in addition to also perform activities of gathering and discussing jazz music. They also always active in the hold and follow jazz events in the area as well as national.